Pharmacotherapeutic potential of pomegranate in age-related neurological disorders - Emami Kazemabad, Mohammad Javad; Asgari Toni, Sara; Tizro, Neda; Dadkhah, Parisa Alsadat; Amani, Hanieh; Akhavan Rezayat, Shima; Sheikh, Zahra; Mohammadi, Mohammad; Alijanzadeh, Dorsa; Alimohammadi, Farnoosh; Shahrokhi, Mehregan; Erabi, Gisou; et al. (Frontiers in Aging Neuroscience, 2022)
Age-related neurological disorders [AND] include neurodegenerative diseases [NDDs] such as Alzheimer's disease [AD] and Parkinson's disease [PD], which are the most prevalent types of dementia in the elderly. It also includes other illnesses such as migraine and epilepsy. ANDs are multifactorial, but aging is their major risk factor. The most frequent and vital pathological features of AND are oxidative stress, inflammation, and accumulation of misfolded proteins. As AND brain damage is a significant public health burden and its incidence is increasing, much has been done to overcome it. Pomegranate (Punica granatum L.) is one of the polyphenol-rich fruits that is widely mentioned in medical folklore. Pomegranate is commonly used to treat common disorders such as diarrhea, abdominal pain, wound healing, bleeding, dysentery, acidosis, microbial infections, infectious and noninfectious respiratory diseases, and neurological disorders. In the current review article, we aimed to summarize the data on the pharmacotherapeutic potentials of pomegranate in ANDs.